Laulāto manta laulāto likumiskajās mantiskajās attiecībās - Kalniņš, Erlens (Latvijas Universitāte, 2010)
Anotācija Ņemot vērā juridiskajā literatūrā izteikto viedokļu dažādību un nevienveidību tiesu praksē, darbā ir aplūkots laulāto mantas institūts laulāto likumiskajās mantiskajās attiecībās (sk. CL 89.–110.p.). Darba mērķis ir izteikt argumentētu viedokli svarīgākajos problēmjautājumos, t.i., 1) jautājumā par laulāto kopīgās mantas sastāva un tās sadalījuma laulāto starpā noteikšanu, kur būtiska nozīme ir likuma noteikumiem par laulāto pierādīšanas pienākumu, 2) jautājumā par viena laulātā rīcību ar laulības laikā iegūto mantu un šādas rīcības tiesiskajām sekām, kur būtiska nozīme ir likuma noteikumiem par trešo personu (labticīgo ieguvēju) aizsardzību, un 3) jautājumā par laulāto kopīgās mantas dalīšanas pareizu izpratni. Lai sasniegtu šo mērķi, darbā ir noskaidrots „mantas” jēdziens, aplūkoti laulāto mantas veidi un to rašanās (iegūšanas) priekšnoteikumi, analizētas laulāto mantas masu mijiedarbības sekas un piedāvāts risinājums tam, kā tiesību tālākveidošanas ceļā pamatot laulātā tiesību uz atbilstošu atlīdzību par viņa izdarīto ieguldījumu otram laulātajam atsevišķi piederošajā mantā. Darbā īpaša uzmanība ir veltīta CL 89.p.2.d. un 91.p.2.d. regulētajam laulāto pierādīšanas pienākumam un tiesiskajām prezumpcijām, kas laulātos atbrīvo no šī pienākuma, kā arī ir aplūkoti un analizēti tiesību labticīgas iegūšanas priekšnoteikumi un tiesiskās sekas (sk. CL 90.p.3.d., 994.p., ZGL 1.p.). Bez tam darbā ir plaši analizēta laulāto kopīgās mantas dalīšanas kārtība (sk. CL 109.p. 3., 4.d.) un kontekstā ar šo jautājumu konkretizēts CL 108.p. un 110.p.2.d. nostiprinātais „trešo personu iegūto tiesību aizsardzības princips”.

Annotation This thesis is devoted to the concept of ‘matrimonial property’ under statutory matrimonial property regime (see Sections 89–110 of the Civil Law). The objective of the thesis is to express a well-reasoned point of view (to provide a uniform solution) as to important problem issues, i.e. 1) the issue related to determination of the composition of joint matrimonial property and division thereof (incl. separation of joint property from the separate property of each spouse) where significant role is played by the provisions of law imposing the burden of proof on spouses; 2) the issue related to acts by one spouse with the property acquired during the course of marriage (in particular, immovable property) and legal consequences of such acts where significant role is played by the provisions of law protecting third parties (acquirers in good faith); and 3) the issue related to correct understanding of the division of joint matrimonial property where it is important to determine the objective of such division. As a result of analysis of rules of law, case law and legal literature, there are conclusions and suggestions provided in this thesis on how to interpret and apply the provisions of law governing the above mentioned issues. Considering that Sections 89–110 of the Civil Law governing the statutory matrimonial property regime as applicable today are drawn based on respective provisions of 89–110 of the Civil Law dated 1937 (by harmonising them with the principle of equality between spouses) the first part of the thesis explores the basic provisions of matrimonial property concept, which set forth ‘husband’s management system’ (and which were applicable in late 30-ies of 20th century), and basic provisions governing the so called ‘equal spouses’ management system’ nowadays. It is concluded in this thesis that both systems are based on the so called ‘principle of separate ownership’. In the second part of the thesis, opinions on all three above mentioned problem issues expressed in the existing legal literature and case law have been summarised and described, reasons (causes) of variety of existing opinions have been clarified, as well as criteria (principle of separate ownership, concept and types of matrimonial property, aggregations of property, objective of separation of joint property of spouses) have been identified, according to which criteria a uniform solution needs to be found in relation to the said issues. 2 The third part of the thesis reviews the term ‘property’ (its legal nature, contents and types thereof, principle of surrogation, as well as the issue related to segregating the property from similar aggregations). In consideration of the concept of property the thesis establishes the concept of ‘matrimonial property’, types thereof and aggregations of matrimonial property, as well as analyses the legal segregation of aggregations of property of the spouses. In addition, this part analyses the issue related to interaction of aggregations of matrimonial property, reasons thereof and legal consequences in case of termination of marriage. In the fourth part, the concept of ‘separate property’ of each spouse has been reviewed and types of such property, i.e. the basis of creation (acquisition) thereof, as set forth in Section 91, Paragraph 1 of the Civil Law, have been analysed. Particular attention is devoted to the contract on designation of separate property (see Section 91, Paragraph 1, Sub-Paragraph 1 of the Civil Law) and to the income from separate property of one spouse (legal nature of such income) with the participation of other spouse (see Section 91, Paragraph 1, Sub-Paragraph 1 of the Civil Law in the light of Section 89, Paragraph 2 of the Civil Law). The fifth part of the thesis explores the concept of ‘joint property’ of spouses, basis of creation (acquisition) thereof, issue related to division of joint matrimonial property (or proportion of ownership) between the spouses, as well as
Matrimonial property under statutory matrimonial property regime
Elektroniskā versija nesatur pielikumus
Keywords: Juridiskā zinātne; Tiesību zinātne